Aplikasi Pengenalan Relief Candi Borobudur Secara Online Dan Offline Menggunakan Html 5 - Firmando, Okky Dian, Dedi ary prasetya, S.T., M.Eng, Ratnasari N R, S.T.,M.T (2016)
Borobudur is a Buddhist temple located in Magelang, Central Java. This monument consists of six square terrace on which there are three circular courtyard, decorated with 2672 relief panels and 504 buddhist statues. Borobudur is one of the historical heritage that must be preserved. The preservation of Borobudur temple is made in digitizing. This study goal to introduction how to make the program application relief Borobudur temple by online and offline. Because of that, everyone can learn about the history of the Borobudur temple, introducing each menu and the meaning contained in it. Method of Presentation of information is done with a web-based which has the capability of distributed and dynamic . The web application is built using HTML5 assisted with CSS 3 and JavaScript . HTML 5 is used to present data with images so that the display becomes unresponsive . CSS 3 functions to display each element and Javascript to create a more interactive display . Implementation of this application is made to be responsive so that it can be used for different types of browsers , both online and offline . The results showed the number of websites there are 142 pictures, the menu of homepages resolution 460x287 pixel, relief arupadhatu 17 resolution 800x533 pixel, rupadhatu 120 resolution 700x250 pixel and kamadhatu 4 resolution 700x250 pixel. The number of data tables there any menu website, relief which contains many description for each level of relief and the menu location is designed in accordance can open use desktop and mobile. Keyword: relief Borobudur, HTML 5, website